Heterologous expression of the apple hexose transporter MdHT2.2 altered sugar concentration with increasing cell wall invertase activity in tomato fruit. Issue 2 (17th August 2019) - Wang, Zhengyang; Wei, Xiaoyu; Yang, Jingjing; Li, Huixia; Ma, Baiquan; Zhang, Kaikai; Zhang, Yanfeng; Cheng, Lailiang; Ma, Fengwang; Li, Mingjun
Summary: Sugar transporters are necessary to transfer hexose from cell wall spaces into parenchyma cells to boost hexose accumulation to high concentrations in fruit. Here, we have identified an apple hexose transporter (HTs), MdHT2.2, located in the plasma membrane, which is highly expressed in mature fruit. In a yeast system, the MdHT2.2 protein exhibited high 14 C‐fructose and 14 C‐glucose transport activity. In transgenic tomato heterologously expressing MdHT2.2, the levels of both fructose and glucose increased significantly in mature fruit, with sugar being unloaded via the apoplastic pathway, but the level of sucrose decreased significantly. Analysis of enzyme activity and the expression of genes related to sugar metabolism and transport revealed greatly up‐regulated expression of SlLIN5, a key gene encoding cell wall invertase (CWINV), as well as increased CWINV activity in tomatoes transformed with MdHT2.2 . Moreover, the levels of fructose, glucose and sucrose recovered nearly to those of the wild type in the sllin5 ‐edited mutant of the MdHT2.2 ‐expressing lines. However, the overexpression of MdHT2.2 decreased hexose levels and increased sucrose levels in mature leaves and young fruit, suggesting that the response pathway for the apoplastic hexose signal differs among tomato tissues. The present study identifies a new HTs in apple that is able to take up fructose and glucose into cells and confirms that the apoplastic hexose levels regulated by HT controls CWINV activity to alter carbohydrate partitioning and sugar content.